1976
DOI: 10.1002/cjce.5450540604
|View full text |Cite
|
Sign up to set email alerts
|

Bubble swarm characteristics in bubble columns

Abstract: New correlations have been proposed for estimation of gas phase holdup, characteristic velocity, interfacial area for mass transfer and mean bubble size of bubble swarms under dispersed and fluidized operation of bubble columns employing singleand multi-orifice distributors. The analysis of results include available literature data of other investigators. ubble column operation in both dispersed and B fluidized regimes has become of major commer-cia1 interest and a considerable relevant literature has now deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 15 publications
3
42
1
1
Order By: Relevance
“…Kumar et al [196] presented the ε G data for air in several liquids and found that their own and the previous investigators' data can be correlated using Equation (11) as a function of the dimensionless gas velocity,…”
Section: Scheme Of Correlations By Lockett and Kirkpatrickmentioning
confidence: 99%
“…Kumar et al [196] presented the ε G data for air in several liquids and found that their own and the previous investigators' data can be correlated using Equation (11) as a function of the dimensionless gas velocity,…”
Section: Scheme Of Correlations By Lockett and Kirkpatrickmentioning
confidence: 99%
“…Both pressure control valve (2) and pressure gauge (4) were used for measuring the pressure drop across the air diffuser. The liquid-film apparatus (LFFA) (9) was installed at the surface water over the air diffuser. The schematic drawing of the LFFA is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Godbole et al (1984) proposed a correlation for gas holdup prediction in CMC solutions. Most of the works in bubble columns dealing with gas holdup measurement and prediction are based on deep bubble beds (Hughmark, 1967;Akita and Yoshida, 1973;Kumar et al, 1976;Hikita et al, 1980;Kelkar et al, 1983;Behkish et al, 2007). A unique work concerned with gas holdup ε G under homogeneous bubbling conditions was published by Hammer et al (1984).…”
Section: Estimation Of Gas Holdupmentioning
confidence: 99%